Is STAT3 and PTEN Expression Altered in Canine Prostate Cancer?. Issue 2 (August 2016) - Lin, H.-Y.; Palmieri, C.
Summary: Signal transducer and activator of transcription 3 (STAT3) and phosphatase and tensin homologue (PTEN) are, respectively, an oncogene and tumour suppressor gene whose dysregulated expression in human prostate cancer is associated with increased malignancy and poor prognosis. Both markers were evaluated in 12 samples of canine benign prostatic hyperplasia (BPH) and 17 canine prostatic carcinomas (PCs) by immunohistochemistry, to understand their possible role in canine prostate carcinogenesis. STAT3 was expressed in 25% and 82.35% of BPH and PC, respectively, with a significantly higher number of STAT3-positive cells in malignant compared with hyperplastic lesions. Three PCs had occasional nuclear expression of STAT3. PTEN was expressed in BPH and PC with a similar distribution and percentage of positive cells; however, four PCs were PTEN negative. Solid PCs contained more STAT3-positive and fewer PTEN-positive cells compared with the other subtypes. A reduced number of PTEN-positive cells was observed in PCs with a high Gleason score (GS10), while no association was demonstrated between STAT3 expression and Gleason score. The data suggest that overexpression of STAT3 and downregulation of PTEN may be an important step in canine prostate carcinogenesis and both markers may be related to the histological subtypes of PC and the degree of differentiation of neoplastic cells.